Development of sensitive analytical methods for the determination of thallium at trace levels by slotted quartz tube flame atomic absorption spectrometry - Ari, Betul; Bakirdere, Sezgin; Ataman, O. Yavuz (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
A simple, sensitive and economical technique is needed for the determination of thallium and this study demonstrates the different analytical strategies were developed using atomic absorption spectrometry (AAS). In order to improve the sensitivity of flame atomic absorption spectrometry (FAAS), a basic slotted quartz tube (SQT) was used for the thallium determination. In the first strategy, mixing propanol (100 mu L) and Tl standard solution (500 mu L) under the optimum conditions, namely solvent assisted SQT-FAAS, provided 4.49 folds enhancement in detection power with the help of better nebulization efficiency and/or atomization of analytes. Furthermore, SQT was used as an atom trap, AT as the second strategy. In this method, analyte atoms were trapped for 5.0 min on the SQT inner surface under the lean flame. In addition, a novel analytical method was developed using an inner surface coated SQT with metals with low volatility (palladium, tungsten, molybdenum, zirconium, tantalum, osmium and titanium). Under the all optimum conditions, limit of detection values were found to be 38 ng(-1) and 3.5 ng(-1) for SQT-AT-FAAS and Os-Coated-SQT-AT-FAAS methods, respectively. 319 folds improvement in detection power was obtained by Os-Coated-SQT-AT-FAAS method with respect to conventional FAAS.
Keywords: Atomic absorption spectrometry; Atom trapping; Coated slotted quartz tube; Thallium; GENERATION; HEALTH; LEAD; ATOMIZATION; SELENIUM; CADMIUM; BISMUTH; INDIUM; TRAPS; ZINC; Spectroscopy